Microsoft encarta 98 deluxe encyclopedia - Microsoft Home (Firm) (Microsoft Home, 1997)
A multimedia encyclopedia with more than 32,000 articles, plus: several hours of sound, including spoken language; illustrations; video clips and animations; maps; games.